From foundation to inspiration: implementing screening for distress (6th Vital Sign) for optimal cancer care—international leadership perspectives on program development. Issue 2 (23rd April 2021) - Bultz, Barry D.; Watson, Linda; Loscalzo, Matthew; Kelly, Brian; Zabora, James
Abstract : Abstract: The principles of whole patient care in cancer and the evidence regarding the benefits of screening for distress provide the impetus for innovation in implementation of psychosocial oncology programs. This includes the creation of new ways of integrating psychosocial assessment in patient reported outcomes and linking this to models of interdisciplinary collaborative care. Screening for distress can itself promote engagement of patients and families/carers in their care. To achieve this, recognition of the broader interpersonal and social context of cancer and related concerns for patients in such screening practices is encouraged. This article will lay the foundation for the successful implementation of clinical distress screening programs and then outline strategies that have been demonstrated to be successful in program quality, growth, and resource preservation. A brief overview of historical foundations of screening for distress is provided along with presentation of examples of innovative practice, including evidence of broader benefits of such screening and future challenges to effective program development, along with including recommendations for implementation within cancer care services.